(untitled) (Scripta : English Department Journal, 2025)
This study examines President Prabowo Subianto’s speech at the 11th Developing Eight (D-8) Summit held in Cairo, Egypt, on December 19, 2024. The main objective of this research is to analyze the rhetorical strategies and socio-political dimensions of his address, focusing on themes related to youth empowerment, economic development, and multilateral cooperation. Using a qualitative descriptive method, the research analyzes the official transcript of the speech, employing a qualitative realist approach to identify recurring themes and patterns. The data analysis follows the four-step process of category identification, context-mechanism-outcome configuration, demi-regularities identification, and generative mechanism refinement. Study reveals that President Prabowo’s discourse emphasizes unity, empowerment, and economic collaboration, with a strong focus on the potential of the D-8 nations as a powerful economic bloc. He uses diplomatic and inclusive language to foster solidarity, while presenting the blue economy as a strategic growth opportunity. Moreover, the speech positions the D-8 as a transformative force in global affairs, advocating for a fairer international order. The findings underscore how strategic rhetoric serves to mobilize cooperation and reinforce Indonesia’s leadership role in promoting sustainable development and regional stability. This analysis contributes to understanding the intersection of political discourse and diplomatic practices in multilateral settings.